2006
DOI: 10.1074/jbc.m513782200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation-dependent Epigenetic Regulation of Dimethylarginine Dimethylaminohydrolase 2 Gene in Trophoblast Cell Lineage

Abstract: Trophoblast cell lineage is established through the first cellular differentiation in mammalian embryogenesis, and its developmental potential is restricted to the extraembryonic tissues contributing solely to the placenta. Several lines of evidence suggest a relative lack of importance of DNA methylation in gene regulation in the extraembryonic tissues when compared with embryonic ones. Here we analyzed the dynamics of epigenetic status in the upstream region of mouse Ddah2 gene, which was found to be specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 37 publications
4
47
1
Order By: Relevance
“…Tomikawa et al previously demonstrated that methylation in this region associated with the silencing of DDAH-2 expression. 55 These results showed a similar trend with the current experiments.…”
Section: Discussionsupporting
confidence: 81%
“…Tomikawa et al previously demonstrated that methylation in this region associated with the silencing of DDAH-2 expression. 55 These results showed a similar trend with the current experiments.…”
Section: Discussionsupporting
confidence: 81%
“…Epigenetic regulation of transcription factors by DNA methylation and histone acetylation have recently been found to regulate imprinted genes, in mouse and humans, and some trophoblast related genes may also be involved in epigenetic regulation: reports suggest NANOG, POU5F1, sal-like protein 3 (SALL3), and serpin inhibitor clade B member 5 (SERPINB5) are involved in epigenetic regulation that influence trophoblast cell proliferation, differentiation, and invasion (Ohgane et al 2004, Dokras et al 2006, Ferguson-Smith et al 2006, Tomikawa et al 2006. However, in the bovine embryo, there is again only limited evidence regarding epigenetic modification of trophoblastspecific genes (Kremenskoy et al 2006a(Kremenskoy et al , 2006b.…”
Section: Roles Of Trophoblast-specific Genes From Gastrulation To Permentioning
confidence: 99%
“…Non-CpG methylation in mammals is quite rare, whereas non-CpG methylation as CNG (N can be any base) is common in plants [8], bacteria [9,10] and yeast [11]. In mammals, DNA methylation of CpGs is involved in various phenomena from development through gene silencing, splicing, stabilizing and chromatin remodeling [1,[12][13][14][15][16][17][18][19][20][21]. In contrast, the biological role of non-CpG methylation in mammals is unknown.…”
mentioning
confidence: 99%